Nanocápsulas de amido via nanoemulsões múltiplas como carreadores de drogas lipofílicas - Pereira, Stéfano Arrais (2019)
Hospital fungal infections from Candida pathogens are associated with the formation of biofilms, which are related to the increased mortality of immunocompromised patients. The use of formulations with sustained release profile aims to prolong the period in the active therapeutic range. From this problem, the synthesis of hydroxyethyl starch nanocapsules via multiple nanoemulsion is presented as an alternative, since its core-shell morphology enables the encapsulation of low water solubility actives, such as clove essential oil (CEO) and lapachol, which have therapeutic potentials, highlighting the microbiological activity of the OEC. Clove oil as well as lapachol were characterized for structural analysis and composition, Chromatography Gas coupled Mass Spectrum (CG-MS) and High Performance Liquid Chromatography (HPLC) respectively, as well as Fourier Transformation Infrared (FT-IR) and Nuclear Magnetic Resonance (NMR) for both bioactive. The synthesized nanocapsules were characterized by FT-IR, where characteristic bands of polyurethane formation from the hydroxyethyl starch crosslinking reaction were observed. By Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM), it is possible to observe the formation of the core-shell structure of the nanocapsules. In addition, Dynamic Light Scattering (DLS) analysis showed that Synthesized capsules were less than 350 nm in size and had moderate colloidal stability. The encapsulation efficiency (EE%) of the nanosystems was calculated and the values obtained were 73.47% for lapachol systems and 76.89% for OEC systems. The diffusion tests of the systems showed that free lapachol diffused 98.89% in 24 h and the same encapsulated presented maximum release of 47.56%, showing the system efficacy in prolonging the drug release. The nanocapsules had their antifungal potential tested against the candida parapsopolis and candida krusei strains, in which the free lapachol showed no activity. However, nanocapsules control and nanocapsules B and OEC showed activity with Minimum Inhibitory Concentration (MIC) of 0.78% and 3.14 ppm respectively and against Candida parapsopolis and 0.74% and 1.57 ppm against Candida krusei. Showing the efficiency of the system in potentiating the antifungal activity of the drug.